2020
DOI: 10.1021/acsbiomaterials.0c01220
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Dynamics Study on the Water Mobility and Side-Chain Flexibility of Hydrated Poly(ω-methoxyalkyl acrylate)s

Abstract: Intermediate water (IW) is known to play an important role in the antifouling property of biocompatible polymers. However, how IW prevents protein adsorption is still unclear. To understand the role of IW in the antifouling mechanism, molecular dynamics simulation was used to investigate the dynamic properties of water and side-chains for hydrated poly­(ω-methoxyalkyl acrylate)­s (PMCxA, where x indicates the number of methylene carbons) with x = 1–6 and poly­(n-butyl acrylate) (PBA) in this study. Since the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
23
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 10 publications
(25 citation statements)
references
References 61 publications
1
23
0
Order By: Relevance
“…MD simulations investigating the dynamic properties of water molecules and side chains of hydrated PMEA and its analogs indicated that polymer materials with a robust hydration layer showed better biocompatibility. 18 The thermodynamic properties of PMEA and PHEMA have also been explored. The free energy profiles of these materials were obtained using MD calculations to evaluate their protein resistances.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…MD simulations investigating the dynamic properties of water molecules and side chains of hydrated PMEA and its analogs indicated that polymer materials with a robust hydration layer showed better biocompatibility. 18 The thermodynamic properties of PMEA and PHEMA have also been explored. The free energy profiles of these materials were obtained using MD calculations to evaluate their protein resistances.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Another study, where MD simulations were performed to identify the structure of IW in hydrated PMEA and its analogs, suggested that IW molecules enhance the flexibility of the polymer side chains. MD simulations investigating the dynamic properties of water molecules and side chains of hydrated PMEA and its analogs indicated that polymer materials with a robust hydration layer showed better biocompatibility …”
Section: Introductionmentioning
confidence: 99%
“…In this study, we developed two kinds of PMEA models: one is a widely used force field model that has been employed in previous MD studies ,, for the general purpose, for example, GAFF, OPLS, and so forth (model 1); the other is the model with the lone-pair VSs located on the carbonyl oxygen O 1 and the methoxy oxygen O 3 (model 2), as discussed in the Methods section. To determine the influences of the introduction of the VSs on the hydrated structure of the side chain of PMEA, we preliminarily carried out MD simulations consisting of one solute MEA in water, using model 1 and model 2, respectively, and calculated the RDFs between the MEA oxygens (O 1 , O 2 , and O 3 ) and water oxygen (O w ).…”
Section: Resultsmentioning
confidence: 99%
“…Molecular dynamics (MD) computer simulation is another powerful tool for investigating the H-bonding structure in an aqueous environment, and some characteristic interactions between water and PMEA have been discussed. Vibrational spectroscopy calculations by MD simulations are also useful for interpreting experimentally observed vibrational spectra. , Recently, Kuo et al systematically examined the H-bonding states of water in PMEA and its analogue based on their classification of water mentioned above. In particular, the velocity–velocity autocorrelation functions of water molecules sorbed into PMEA were calculated to discuss the vibrational spectra for the OH stretching region of water interacting with PMEA . However, the reproducibility of the calculated spectra may not be satisfactory, particularly at a low water content, because the spectra for the entire water-concentration range show a peak around 3400 cm –1 rather than around 3600 cm –1 , and no peak shift was observed in the MD simulation.…”
Section: Introductionmentioning
confidence: 99%
“…The theoretically evaluated BW1 content was found to negatively correlate with the experimentally measured amounts of adhered platelet and adsorbed fibrinogen on the PMC y A-coated surface ( y = 2–6). , Moreover, the flexibility of the side chains and the mobility of the bound water (BW) might have some influence on the protein adsorption . For example, the poor resistance of protein adsorption for PMC1A was ascribed to the highest mobility of BW1, whereas the best resistance of protein adsorption for PMC3A was attributed to the highest content of the side chain binding with two BW1 molecules …”
Section: Introductionmentioning
confidence: 99%